Gray Code Image Encryption using Knight Tour Scrambler - Singh, Manjinder (My University, 2016)
Secured and timely transmission of data is always an important aspect for an organization. In the encryption process the failure rate of keys and processing time are directly related with the security of cryptographic model in a Multi-node Network (MN) The use of strong encryption algorithms almost make it impossible for a hacker to get access of node which is being protected by multiple keys. Data security is an essential component of an organization in order to keep the information safe from various competitors. It helps to ensure the privacy of a user from others. In present scenario most of the information is being collected, processed and stored by the computers and further transmitted across the networks therefore, there is a need to protect the network in order to keep the data confidential. Keeping in view the importance of multiple keys for secure data transmission this work incorporates the use of multiple keys. Current aspects of cryptography and need of data security in communication and various security constraints are discussed in the beginning of this thesis. The work done by the various researchers in the field of cryptography has also been discussed. Observations from literature survey, problem formulation, objectives and research mythology has been formulated to design a new methodology. The proposed scheme meets the objectives such as optimization of variance, correlation co-efficient, covariance, standard deviation. Also the encryption and decryption time has been analysed for fast processing and secure communication. After presenting the proposed scheme, it has been compared with existing schemes such as DES, TDES and AES on the basis of encryption and decryption time. Finally, conclusions and the future scope of the proposed work have been mentioned.
Keywords: Image Encryption